2021
DOI: 10.4103/ajns.ajns_480_20
|View full text |Cite
|
Sign up to set email alerts
|

Primary intraosseous xanthogranuloma in adult cervical spine: A case report of benign cause of lytic bone lesion

Abstract: Lytic lesions in adult spine are a common manifestation of aggressive disease such as primary bone tumor, metastasis, myeloma, or infectious pathology. Xanthoma arising in the spine with purely intraosseous component is an extremely rare occurrence with only six cases reported in the adult population, none in the cervical region. We report the first case of primary xanthoma of the cervical spine in a 50-year-old male solely confined to osseous compartment. The imaging mimics of lytic lesion with expansile mass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 21 publications
(46 reference statements)
0
3
0
Order By: Relevance
“…Both lytic and sclerotic lesions in imaging studies have been reported. However, there have been few previous reports describing the histopathological findings in skeletal lesions 8,10 . In this case, features of the lesion obtained from the retro-odontoid mass were similar to those from a tumor that bulged posteriorly from the C1-C2 facet joint.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both lytic and sclerotic lesions in imaging studies have been reported. However, there have been few previous reports describing the histopathological findings in skeletal lesions 8,10 . In this case, features of the lesion obtained from the retro-odontoid mass were similar to those from a tumor that bulged posteriorly from the C1-C2 facet joint.…”
Section: Discussionmentioning
confidence: 99%
“…C ervical spine involvement in patients with XD has rarely been reported 10 . XD with skeletal involvement usually follows a slow clinical course similar to its progression in other tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation